Overweight and obesity in Slovak high school students and body composition indicators: a non-randomized cross-sectional study - Bibiana Vadasova; Pavol Cech; Viera Smerecka; Jan Junger; Martin Zvonar; Pavel Ruzbarsky (BMC, 2016)
Abstract Background Physical development can be considered as an indicator of the overall health status of the youth population. Currently, it appears that the increasing trend of the prevalence of obesity among children and youths has stopped in a number of countries worldwide. Studies point to the fact that adolescence is a critical period for the development of obesity. Body mass index (BMI) seems to be an orientation parameter in the assessment of prevalence of obesity which is not sufficient for more accurate identification of at risk individuals. The purpose of this study was to evaluate association between BMI percentile zones as health-risk for being overweight and obese and body composition indicators in high-school students from the Prešov (Slovakia) region. Methods A non-randomized cross-sectional study in high school students from the Prešov (Slovakia) region was conducted. The research sample consisted of 1014 participants (boys n = 466, girls n = 549). Body composition was measured using direct segmental multi-frequency bioelectrical impedance analysis (DSM-BIA). To examine the association between obesity and selected body composition indicators, Kruskal-Wallis ANOVA and Eta2 were used. The relationship between selected body composition indicators and percentile BMI zones was determined using the Kendall tau correlation. Results In groups with different BMI percentile zones (normal weight, overweight, obese), ANOVA showed significant differences for girls and boys (p ˂.05) with high effect size (η2 ˂.26) in body weight, body fat mass index, body fat percentage, fat free mass index, fat-free mass percentage, visceral fat area, waist-to-hip ratio, waist circumference, protein mass and mineral mass. The highest degree of correlation among boys was between BMI values indicating overweight and obesity and fat free mass index and waist circumference, respectively (τ = .71, τ = .70, respectively). In girls, the highest correlation was found between classification of BMI percentile zones and waist circumference (t = .78). Conclusion The characteristics of body composition are very useful determinants of health and nutrition status. Our data revealed a direct association between BMI value and chosen body composition indicators. The most accurate indicator of overweight and obesity in our study appears to be waist circumference for both male and female population.